2019
DOI: 10.1016/j.fsi.2019.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Immune response modulation upon sequential heterogeneous co-infection with Tetracapsuloides bryosalmonae and VHSV in brown trout (Salmo trutta)

Abstract: 22 Highlights 42 -First comprehensive transcriptional study on a sequential heterogeneous co-infection in fish 43 -Large primer set optimised for immune gene expression screenings in brown trout 44 -Significant correlations between pathogenesis and innate and adaptive immune genes expression 45 -Favourable modulations of T helper subsets activity seen in PKD/VHS co-infected fish 46 -Enhanced antiviral response seen in PKD/VHS co-infected fish 47 48

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…All pathoanatomical changes in moribund fish examined in this study corresponded to the typical proliferative kidney disease signs [ 26 ], but a possible role of coinfection cannot be ruled out completely because the PRV-3-positive fish were also positive for T. bryosalmonae . A potentiating effect of T. bryosalmonae and a viral agent (VHSV) on the changes of the immune system of salmonids was previously described by Gorgoglione et al [ 37 ]. Other studies confirmed that a Raphidascaris acus infection prolonged PKD-related gross changes in brown trout kidneys [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All pathoanatomical changes in moribund fish examined in this study corresponded to the typical proliferative kidney disease signs [ 26 ], but a possible role of coinfection cannot be ruled out completely because the PRV-3-positive fish were also positive for T. bryosalmonae . A potentiating effect of T. bryosalmonae and a viral agent (VHSV) on the changes of the immune system of salmonids was previously described by Gorgoglione et al [ 37 ]. Other studies confirmed that a Raphidascaris acus infection prolonged PKD-related gross changes in brown trout kidneys [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…T. bryosalmonae acts as an immunomodulant [ 48 ] and can potentially cause up to 20% mortality in affected brown trout [ 26 ], with additional coinfections potentiating the pathologic effects [ 37 , 38 ]. Additionally, infections of European brown trout have a larger impact on the health of the infected fish, when compared with rainbow trout [ 40 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The β-defensin family of genes plays a significant role in antibacterial and antiviral immunity in fish [ 27 , 46 , 47 , 48 ]. Previous studies showed up-regulation of β-defensins and other antimicrobial peptide (AMP) genes in the kidney of brown trout infected with the novirhabodvirus viral hemorrhagic septicemia virus (VHSV) [ 49 ]. However, the expression of antimicrobial peptides in the trout olfactory organ had not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that one of the four β-defensin genes studied, omdb-3 , showed a unique expression pattern characterized by a more sustained up-regulation compared to the other three β-defensin genes. Similarly, in VHSV-infected brown trout, omdb-3 expression changes in the kidney differed from those of other AMP genes [ 49 ]. Future studies should determine the unique function of each AMP in the context of nasal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Type I IFN transcripts strongly correlate with viral burden and with the transcription of marker genes encoding for effectors of the IFN antiviral cascade [48,49]. The sustained expression of IGSs, viz MX proteins, ISG-15 or VIPERIN, is a common hallmark adopted in fish immunology as a measure of the antiviral state induced upon viral infections [50][51][52][53][54], and heterogeneous co-infections [55,56]. As such, a potential role for NV in suppressing host innate immunity would represent a novel function unique to Novirhabdovirus.…”
Section: Introductionmentioning
confidence: 99%